2015
DOI: 10.1056/nejmc1504715
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy for Ischemic Stroke

Abstract: The utility of intravenous tissue plasminogen activator (IV t-PA) in improving the clinical outcomes after acute ischemic stroke has been well demonstrated in past clinical trials. Though multiple initial small series of endovascular stroke therapy had shown good outcomes as compared to IV t-PA, a similar beneficial effect had not been translated in multiple randomized clinical trials of endovascular stroke therapy. Over the same time, there have been parallel advances in imaging technology and better understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(28 citation statements)
references
References 62 publications
2
25
0
1
Order By: Relevance
“…In accordance with the latest trials on MT, 5,[35][36][37][38][39] our study population demonstrated a significant benefit from successful recanalization with significantly better clinical and imaging outcomes than nonsuccessfully recanalized patients. Although selection of our patient population was not ideal compared with the controlled thrombectomy trials, 5,35,38 our study has the advantage of reflecting daily clinical routine better.…”
Section: Estimation As Malignant Mismatch Profilesupporting
confidence: 86%
“…In accordance with the latest trials on MT, 5,[35][36][37][38][39] our study population demonstrated a significant benefit from successful recanalization with significantly better clinical and imaging outcomes than nonsuccessfully recanalized patients. Although selection of our patient population was not ideal compared with the controlled thrombectomy trials, 5,35,38 our study has the advantage of reflecting daily clinical routine better.…”
Section: Estimation As Malignant Mismatch Profilesupporting
confidence: 86%
“…[7][8][9] For this study, home-time was defined as the total number of days alive and out of acute care hospitals, inpatient rehabilitation, or skilled nursing facilities from the first day forward of index hospital admission for acute ischemic stroke. Inpatient days in these settings were identified in Medicare inpatient and skilled nursing facility claims.…”
Section: Discussionmentioning
confidence: 99%
“…5 This has been proposed as a graded and objective functional outcome measure for international acute ischemic stroke trials and has been shown to correlate with mRS in clinical trial populations and demonstrate gains in response to effective stroke therapies, such as intravenous tissue-type plasmiogen activator and mechanical thrombectomy treatment. [5][6][7] More recently, stroke survivors have identified home-time as a meaningful and highly prioritized outcome. [8][9][10] Home-time may thus represent an outcome measure that is more easily understood by patients with stroke, their families, and clinicians.…”
mentioning
confidence: 99%
“…After successful clinical trials in patients with occlusion of a major intracranial artery, mechanical thrombectomy (MT) with stent retrievers adds a novel therapeutic option in patients with acute ischemic stroke (AIS) [ 1 , 2 , 3 ]. As MT is only applicable in approximately 5%–10% of patients with ischemic stroke, intravenous thrombolysis (IVT) using recombinant tissue plasminogen activator is still the treatment of choice for most patients with AIS [ 4 ].…”
Section: Introductionmentioning
confidence: 99%